Multidisciplinary correlates of table tennis participation in children: a concept mapping study - Liu, Jiang (Frontiers in Public Health, 2025)
BackgroundTable tennis engages a combination of motor, cognitive, and psychosocial skills, demanding quick decision-making, precise coordination, and interpersonal interaction. This study explored the relationship between participation in table tennis training and improvements in children’s motor abilities, cognitive development, and psychological resilience.MethodsA total of 312 children (156 boys, 156 girls), aged 8–14 years, participated in a 12-month structured table tennis program. Motor performance was evaluated via agility drills, simple reaction time, and hand–eye coordination tasks. Cognitive outcomes were assessed using the Stroop Test and the Wisconsin Card Sorting Test (WCST). Psychosocial indicators encompassed self-efficacy, peer interactions, and perceived stress. Structural equation modeling (SEM) was employed to examine hypothesized direct and indirect associations among these domains.ResultsLonger training duration was significantly associated with improved reaction time (r = −0.42, p < 0.001), agility (r = −0.38, p < 0.001), and hand-eye coordination (r = 0.46, p < 0.001). WCST errors (r = −0.38, p < 0.001) and Stroop response time (r = −0.42, p < 0.001) decreased. Self-efficacy (r = 0.41, p < 0.001) and social competence (r = 0.42, p < 0.001) increased, while perceived stress (r = −0.39, p < 0.001) and antisocial behavior (r = −0.43, p < 0.001) declined. Structural equation modeling revealed significant associations among motor, cognitive, and psychosocial outcomes.ConclusionThe findings indicate that structured table tennis training is associated with enhancements in motor coordination, executive functioning, and psychosocial well-being. These results highlight its potential value as an effective component of school-based developmental programs.